MANAJEMEN PENERIMAAN SISWA BARU - Nizarman Nizarman (UNIVERSITAS BENGKULU, 2015)
This study aims to evaluate the management of new admissions in the Senior High School 3 Seluma accordance with special standars. The research method used is descriptive comparative. Data collection techniques used in this study are interviews, documentation, and observation. The results showed the new admissions management already set standards in all aspects of planning new admissions, organizing new admissions, the implementation of new admissions in accordance with the standards, and reporting of new admissions, while formonitoring and evaluation new admissions are not in accordance with the standards.Key words: management, acceptance, new students